Pengaruh Media Pembelajaran Berbasis Genially terhadap Hasil Belajar Siswa dalam Pembelajaran Pendidikan Pancasila Kelas IV Materi Hak dan Kewajiban di UPTD SD Inpres Palsatu Kota Kupang - Banamtuan, Mersi; Ga, Paulina Riwu; Kota, Martha Khristina (ARZUSIN, 2025)
This study is motivated by the low learning outcomes of students, which are attributed to the limited use of engaging and interactive learning media. The aim of this study is to determine the significant effect of using Genially-based learning media on students' learning outcomes in the Pancasila Education subject. The study employs a quantitative approach with the One Group Pre-Experimental Design method and a One Group Pretest-Posttest Design. The research subjects were fourth-grade students at UPTD SD Inpres Palsatu, Kota Kupang, focusing on the topic of rights and obligations. The results show a significant improvement in learning outcomes following the implementation of Genially-based media, as evidenced by the increase in the average score from 61.33 in the pretest to 83.33 in the posttest. The hypothesis test using the paired sample t-test produced a significance value of 0.000 (p < 0.05), indicating a significant difference between the pretest and posttest results. Thus, it can be concluded that Genially-based learning media has a significant effect on improving students' learning outcomes. The implications of this study highlight the importance of innovative, interactive digital learning media in enhancing instructional effectiveness, particularly at the elementary school level.